Retrospective View of Two Years of Colposcopy Practice in a Gynecologic Clinic in Cotonou - TOGNIFODE, Véronique; DENAKPO, Justin Lewis; ABOUBAKAR, MOUFALILOU; OGOUDJOBI, OGOURINDÉ MATHIEU; LOKOSSOU, Mègnissè Sèna H. S.; TONATO BAGNAN, Josiane Angeline; PERRIN, RENÉ-XAVIER (My University, 2017)
Objective : To analyse the colposcopy results at the Gynaecological Clinic of Houéyiho. Patients and methods : Retrospective, descriptive and analytical studies were conducted by the Clinic of Houeyiho in Cotonou from January 2013 to December 2015. Results : 440 women were received in colposcopy including 251 (57%) referred by health workers for VIA (Visual Inspection with Acétique Acid)/VILI (Visual Inspection with Lugol’s Iodine) abnormalities, forty-seven (47) for abnormal smears (10.7%), thirty-eight (38) for metrorrhagia (8.6%). 10% of cases were mainly concerned with post-therapeutic monitoring (six colposcopies of the vagina fundus after hysterectomy for cervical cancer and four after conization). The average age of patients is 41 years within plus or minus 5 years. Forty (40) cases of Grade 1 Atypical Transformation, twenty-nine (29) cases of Grade 2 Atypical Transformation including two (2) cases of leukoplakia (1 post-conization for CINIII, 1 in a HIV+ patient), ten (10) cases of Grade 1 Atypical Transformation/Grade 2 Atypical Transformation association were recorded. A colposcopy biopsy was performed in 95 patients meaning 21.6% of patients. Five biopsies were realized for a cervical neoplasia suspicion and were sent to Pasteur Cerba laboratory in France for the sake of efficiency and rapidity of results. In Grade 1 Atypical Transformation, 66.6% of CIN1 and condylomata plana were noted. Nevertheless, a case of mucinous adenocarcinoma with metaplasia has been discovered in a TAG1 with a 23-year old patient. In Grade 2 Atypical Transformation, the histology reveals 44.4% of CIN 1, 40.7% of severe dysplasia and 11.1% of carcinomas. Conclusion: The colposcopy may be a good screening method with a good colpo-histology agreement in Cotonou. But it’s relatively expensive (20.000 CFA francs) and the reduced number of colposcopists restricts its use in Benin.
Keywords: Colposcopy; Cervical Smear; Precancerous Lesions; Histology; Benin